2016
DOI: 10.1007/s10584-016-1672-7
|View full text |Cite
|
Sign up to set email alerts
|

A commentary on “how to interpret expert judgment assessments of twenty-first century sea-level rise” by Hylke de Vries and Roderik SW van de Wal

Abstract: We clarify key aspects of the evaluation, by de Vries and van de Wal (2015), of our expert elicitation paper on the contributions of ice sheet melting to sea level rise due to future global temperature rise scenarios (Bamber and Aspinall 2013), and extend the conversation with further analysis of their proposed approach for combining expert uncertainty judgments. Aspinall (2013: [BA13]), and welcome this opportunity to clarify the work presented in BA13 and extend the analysis of VW15. The problem of finding a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 9 publications
2
18
0
Order By: Relevance
“…A statistical accuracy below 0.05 is often used as a cut‐off point at which an expert is considered statistically inaccurate (i.e., Bamber et al. , Colson and Cooke ). The 0.05 level is often used in meta‐analyses comparing the weighting and aggregation schemes in the Classical Model literature, but can also be used by the analyst as a cut‐off point at which zero weight may be assigned to the expert's judgment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A statistical accuracy below 0.05 is often used as a cut‐off point at which an expert is considered statistically inaccurate (i.e., Bamber et al. , Colson and Cooke ). The 0.05 level is often used in meta‐analyses comparing the weighting and aggregation schemes in the Classical Model literature, but can also be used by the analyst as a cut‐off point at which zero weight may be assigned to the expert's judgment.…”
Section: Methodsmentioning
confidence: 99%
“…However, Bamber et al. () and Colson and Cooke () found that quantile aggregation is much more overconfident than linear pooling (when assessed using the Classical Model's statistical accuracy measure). To investigate these findings, we extend our analysis to compare how the two methods of equal weighted aggregation can affect judgments.…”
Section: Methodsmentioning
confidence: 99%
“…Higher values indicate an expert's distribution more closely matches the theoretical distribution. A statistical accuracy below 0.05 is often used as a cut‐off point at which an expert is considered statistically inaccurate (ie, Bamber et al and Colson and Cooke). Information (often referred to as informativeness) under the Classical Model measures the degree to which the distribution supplied is concentrated and to which it deviates from a uniform or log‐uniform distribution (which are considered the least informative distributions). It uses the KL divergence measure, which is scale invariant .…”
Section: Methodsmentioning
confidence: 99%
“…Both cases yielded a heavy-tailed distribution for the Antarctic ice sheet and hence total sea level. Additional interpretation of Bamber and Aspinall (2013) was made by De Vries and Van de Wal (2015; see also response by Bamber et al 2016) and was consequently used by de Winter et al (2017). Several other probabilistic projections have been made based on a recent Antarctic ice sheet modelling studying by DeConto and Pollard (2016) (e.g., Kopp et al 2017).…”
Section: Probabilistic Approach To Sea Level Changesmentioning
confidence: 99%